Unravelling chemical cues used by Diachasmimorpha longicaudata (Hymenoptera: Braconidae ) during host search - Devescovi, Francisco; Fernández, Patricia; Bachmann, Guillermo Enrique; Nussenbaum, Ana Laura; Segura, Diego Fernando (FAO-IAEA, 2022)
Poster